Hubungan Self-Care Management Terhadap Kualitas Hidup Pada Penderita DM Tipe 2 Di Kelurahan Jati Wilayah Kerja Puskesmas Andalas Padang - Lola Despitasari; Fitria Alisa; Lenni Sastra; Weny Amelia; Ria Desnita; Fadhila Suci Edrian (Sekolah Tinggi Ilmu Kesehatan YPAK Padang, 2023)
Diabetes Mellitus (DM) Type 2 is a metabolic disorder characterized by a progressive increase in insulin levels against a background of decreased insulin resistance. DM Type 2 requires treatment in managing the disease with self-care management, if blood sugar levels are not controlled it will increase the risk of complications and can affect the quality of life of sufferers. Quality of life is a concept related to the well-being of sufferers physically, psychologically, socially and environmentally. The purpose of this study was to determine the relationship between self-care management and quality of life in patients with DM type 2 at Jati Village, Andalas Health Center, Padang City. This type of analytic research with cross sectional design. The sample is 67 respondents. Sampling technique with purposive sampling. Data were analyzed using the Chi-square test. Based on the results of the study, it was found that 35 respondents (52.2%) had a poor quality of life, and 38 respondents (56.7%) had poor self-care management. The statistical test results obtained a p value of 0.000 (p ≤ 0.05), it can be concluded that there is a relationship between self-care management and quality of life in patients with DM type 2 at Jati Village, the Working Area of ​​the Andalas Padang Health Center. It is expected that nursing services will develop health programs related to self-care management to improve the quality of life in DM type 2 patient.